The Endemic Impact of Covid-19 on the Welfare of Traders at the Susumbolan Market, Tolitoli Regency - Fitri S. Kasim; Hariani Hanapi; Fandrianto K. Muhammad (Formosa Journal of Sustainable Research, 2023)
In March 2019 the world was struck by the emergence of an outbreak of a disease called corona or covid-19. Covid-19 has had an economic, social and environmental impact. The economic impact is the worst because of the effects that have weakened the country's economy. The purpose of this study was to determine the endemic of covid-19 on the welfare of traders at the Susumbolan Market, Tolitoli Regency. This study uses a type of qualitative research. The results showed that the impact of the Covid-19 endemic caused the income level of traders to decrease so that the level of welfare of traders in the Susumbolan Market, Tolitoli Regency, was unable to meet their daily needs which caused the traders' capital to decrease